Edukasi Kader dalam Upaya Pencegahan dan Penanggulangan Stunting di Kecamatan Mondokan Kabupaten Sragen - Anik Lestari; Diffah Hanim (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2020)
Nowadays stunting has become the most observed on nutrition issues by the Indonesian government because stunting does not only cause physical abnormalities but also cognitive impairment in todlers so that as adults they will have low productivity. The aim of this community service was to increase the knowledge of certain community groups (health nutrition cadres) in preventing stunting in todlers. With the process of diffusion of knowledge, it is expected that there will be improvement in behavior of the target audience in carrying out their duties as posyandu cadres. This community service agenda are implemented through two activities. By having lectures and QnA sessions. The second method namely “cerdas cermat” was used to assess whether the counseling material can be understood by the participants. A team answer correctly they will be given a "door prize". The implementation of community service in the form of health education targeting Posyandu cadres in Mondokan Subdistrict, Sragen has been successfully implemented. The cadres were very enthusiastic to participate in the activity. This was indicated by their active participation in asking questions during lectures. In addition, during the game "cerdas cermat" was held, cadres can successfully answer questions related to the material "prevention of stunting". This educational activity needs to be followed up by "training" and "assistance", because if it is only given lecturing once it was feared that cadres could nott apply their new knowledge well.